Design of a Gd‐DOTA‐Phthalocyanine Conjugate Combining MRI Contrast Imaging and Photosensitization Properties as a Potential Molecular Theranostic. (7th October 2014) - Aydın Tekdaş, Duygu; Garifullin, Ruslan; Şentürk, Berna; Zorlu, Yunus; Gundogdu, Umut; Atalar, Ergin; Tekinay, Ayse B.; Chernonosov, Alexander A.; Yerli, Yusuf; Dumoulin, Fabienne; Guler, Mustafa O.; Ahsen, Vefa; et al.
Abstract The design and synthesis of a phthalocyanine – Gd‐DOTA conjugate is presented to open the way to novel molecular theranostics, combining the properties of MRI contrast imaging with photodynamic therapy. The rational design of the conjugate integrates isomeric purity of the phthalocyanine core substitution, suitable biocompatibility with the use of polyoxo water‐solubilizing substituents, and a convergent synthetic strategy ended by the use of click chemistry to graft the Gd‐DOTA moiety to the phthalocyanine. Photophysical and photochemical properties, contrast imaging experiments and preliminary in vitro investigations proved that such a combination is relevant and lead to a new type of potential theranostic agent.